2006
DOI: 10.1186/1472-6750-6-37
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Background: Real-time PCR is the technique of choice for nucleic acid quantification. In the field of detection of genetically modified organisms (GMOs) quantification of biotech products may be required to fulfil legislative requirements. However, successful quantification depends crucially on the quality of the sample DNA analyzed. Methods for GMO detection are generally validated on certified reference materials that are in the form of powdered grain material, while detection in routine laboratories must be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
80
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(81 citation statements)
references
References 27 publications
1
80
0
Order By: Relevance
“…Many studies have been published to determine the more appropriate extraction method for each food matrix in order to minimize the influence of the extraction in the variability of DNA amplification, mainly in the quantification of low copy number target using real time PCR (CANKAR et al, 2006;CORBISIER et al, 2007;FERRARI et al, 2007;PEANO et al, 2004;SMITH;MAXWELL;DE BOER, 2005;SMITH;MAXWELL, 2007;ZIMMERMANN;LÜTHY;PAULI, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been published to determine the more appropriate extraction method for each food matrix in order to minimize the influence of the extraction in the variability of DNA amplification, mainly in the quantification of low copy number target using real time PCR (CANKAR et al, 2006;CORBISIER et al, 2007;FERRARI et al, 2007;PEANO et al, 2004;SMITH;MAXWELL;DE BOER, 2005;SMITH;MAXWELL, 2007;ZIMMERMANN;LÜTHY;PAULI, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…It entails adequate knowledge and sufficient control of several factors, such as the quality of the nucleic acids, appropriate choice of reference materials, comparable amplification efficiencies between calibrants and samples, stability of the event-and reference systems, and the specificity levels of the assays (Shokere et al 2009;Berdal et al 2008;Corbisier et al 2007;Cankar et al 2006;Broothaerts et al 2008 International bodies (ISO 5725 International Organization for Standardization 1994; IUPAC 1988) provide comprehensive standards describing procedures to assess analytical method performance. The Codex Alimentarius Commission recently adopted into the international food code the 'Guidelines on performance criteria and validation of methods for detection, identification and quantification of specific DNA sequences and specific proteins in foods' (Codex Alimentarius Commission 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These authors tested four maize and four soybean samples and found crucial influences on the results of GMO quantification from the extraction technique and sample matrix properties. Although they suggested the development of appropriate extraction techniques for each matrix, the authors also highlighted that for samples with certain compositional specificities, it will be impossible to define strict quality controls, such as acceptance criteria to compare the efficiency of the sample to that of the standard curve, to be introduced to monitor PCR (Cankar et al 2006). Adaptation of DNA extraction protocols for heterogeneous samples will then have to be done by different groups and is most likely unable to be harmonized for all GMO detection work.…”
Section: Discussionmentioning
confidence: 99%
“…The extraction method is therefore key to ensure high yield and quality of the DNA obtained and must be carefully selected or adapted. Cankar et al (2006) have analysed the effects of DNA extraction methods and sample matrices on quantification of GMOs. These authors tested four maize and four soybean samples and found crucial influences on the results of GMO quantification from the extraction technique and sample matrix properties.…”
Section: Discussionmentioning
confidence: 99%